Pengaruh Financial Target, Ineffective Monitoring, Dan Financial Distress Terhadap Fraud Of Financial Reports - Luthfi Miftahul Putri; Yuha Nadhirah Qintharah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2023)
The purpose of this research is to find out the impact of financial financial monitoring, ineffective monitoring and financial distress on fraudulent financial statements directed at companies in industries the property, real estate and construction building in the audit period 2019-2021. Using purposive sampling in the method sampling to obtain a sample of 56 companies. This research used regression analysis panel data of software Eviews version 10. According on this output, that show results financial goals have a significant positive effect on fraudulent financial statements, while ineffective monitoring and financial distress have a significant negative effect impact on fraud reports.